The Endocrine Disruption of Prenatal Phthalate Exposure in Mother and Offspring - Qian, Yiyu; Shao, Hailing; Ying, Xinxin; Huang, Wenle; Hua, Ying (Frontiers in Public Health, 2020)
Phthalates are a group of ubiquitous synthetic endocrine-disrupting chemicals. Fetal and neonatal periods are particularly susceptible to endocrine disorders which prenatal exposure to phthalates cause. There is increasing evidence concerning the potential endocrine-disrupting for phthalates exposure during pregnancy. This article aims to review the endocrine impairment and potential outcomes of prenatal phthalates exposure. Prenatal exposure phthalates give rise to the alterations of thyroid and sex hormone levels in pregnant women and offspring and the disruption of circulating levels of 25-hydroxyvitamin D in mother, which result in adverse maternal and neonatal outcomes such as preterm birth, preeclampsia, glucose disorders in mother and cryptorchidism, hypospadias, as well as shorter anogenital distance in newborns, and growth restriction not only in infants but also in early adolescence and childhood. The relationship of prenatal phthalate exposure with maternal and neonatal outcomes in human beings was often sex-specific associations. Due to the potentially harmful influence of prenatal phthalates exposure, steps should be taken to prevent or reduce phthalate exposure during pregnancy.